Optimizing Lean Manufacturing Efficiency with Novel Line Balancing in the Automotive Exhaust Manufacturing Sector - Tuan, Saravanan Tanjong; Daud, Mohd Radzi Bin Haji Che (International Journal of Membrane Science and Technology, 2023)
This study examined the application of Lean manufacturing tools and a novel approach called line balance loss analysis in optimizing production processes at a Malaysian automotive exhaust manufacturing company. The primary objective was to align production rates with customer demand. Data collection involved two key aspects: gathering production process data for catalytic converters, front pipes, and muffler subassemblies, and acquiring technical data on Lean tools, including the innovative line balance loss analysis method, from one muffler production line. The integration of Lean tools with the new line balance loss analysis approach was found to be crucial. The multi-process/multi-machine line balancing approach went beyond eliminating Non Value Added (NVA) activities and focused on determining manpower requirements and task allocation among operators. The integration of the new line balance loss analysis method improved task distribution across workstations, enhancing overall process efficiency. The study's analysis of Lean tool applications and the innovative line balance loss analysis provided insights into the cellular manufacturing system of the production line. These findings offered valuable information for management decision-making and process improvement, ultimately leading to increased productivity and cost savings for the company.